2022
DOI: 10.21203/rs.3.rs-1404546/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 on carers of people with dementia in the community: Findings from the IDEAL cohort

Abstract: Background Unpaid carers for people with dementia play a crucial role in society. Emerging evidence suggests the COVID-19 pandemic has negatively impacted on carers. Objective To explore the impact of the COVID-19 pandemic on carers for community-dwelling people with dementia and compare responses with pre-pandemic data. Methods Data were collected between September 2020 and April 2021 in England and Wales. Carers were identified from the IDEAL cohort and data were collected either through the telephone, vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…As shown in Table 3, there was no difference between pandemic and prepandemic groups at w1 with an increase in role captivity score between w1 and w2 for the prepandemic group. There was an interaction effect, suggesting that the role captivity score, whilst still increasing, increased to a lesser extent for the pandemic group when compared to the pre-pandemic tent with our previous evidence [29]. Almost all of the studies to date were conducted in the first few months of the pandemic, whereas ours was conducted from 8 months onwards, reflecting a longer-term impact of the pandemic on the carer.…”
Section: Role Captivitysupporting
confidence: 53%
See 1 more Smart Citation
“…As shown in Table 3, there was no difference between pandemic and prepandemic groups at w1 with an increase in role captivity score between w1 and w2 for the prepandemic group. There was an interaction effect, suggesting that the role captivity score, whilst still increasing, increased to a lesser extent for the pandemic group when compared to the pre-pandemic tent with our previous evidence [29]. Almost all of the studies to date were conducted in the first few months of the pandemic, whereas ours was conducted from 8 months onwards, reflecting a longer-term impact of the pandemic on the carer.…”
Section: Role Captivitysupporting
confidence: 53%
“…However, it is noteworthy that a follow up study that included a pre-pandemic control found that whilst positive emotions were still higher for older people, ers believed they were coping well [23]. Our initial 593 study using IDEAL data also reported that carers were 594 generally coping well [29]. burden [1,16,44].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 93%